2020
DOI: 10.1007/s10815-020-01945-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification and rescue of a novel TUBB8 mutation that causes the first mitotic division defects and infertility

Abstract: Purpose Tubulin beta eight class VIII (TUBB8) is essential for oogenesis, fertilization, and pre-implantation embryo development in human. Although TUBB8 mutations were recently discovered in meiosis-arrested oocytes of infertile females, there is no effective therapy for this gene mutation caused infertility. Our study aims to further reveal the infertility-causing gene mutations in the patient's family and to explore whether the infertility could be rescued by optimizing the conditions of embryo culture and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 20 publications
0
10
1
Order By: Relevance
“…Although the two patients have one different mutation site in addition to p.Tyr217Asn, the phenotypes of the two are very similar including MI arrest and Pb1 oocytes with large polar body (Chen et al, 2017b ). Another recurrent mutation p.Ser459Tyr is conserved among different species, but the phenotype of the patient (family 3 II-1) is not completely consistent with that of the patient in previous report (Jia et al, 2020 ). Considering that the PATL2 Y217N mutation recurred in the patients with similar phenotype and is conserved among different species, we chose p.Tyr217Asn in PATL2 (PATL2 Y217N ) as a typical to explore the possible mechanism of PATL2 mutations that cause oocyte maturation defect.…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Although the two patients have one different mutation site in addition to p.Tyr217Asn, the phenotypes of the two are very similar including MI arrest and Pb1 oocytes with large polar body (Chen et al, 2017b ). Another recurrent mutation p.Ser459Tyr is conserved among different species, but the phenotype of the patient (family 3 II-1) is not completely consistent with that of the patient in previous report (Jia et al, 2020 ). Considering that the PATL2 Y217N mutation recurred in the patients with similar phenotype and is conserved among different species, we chose p.Tyr217Asn in PATL2 (PATL2 Y217N ) as a typical to explore the possible mechanism of PATL2 mutations that cause oocyte maturation defect.…”
Section: Discussioncontrasting
confidence: 50%
“…TUBB8 mutations and TRIP13 mutations were identified to cause human oocyte MI arrest (Feng et al, 2016 ; Zhang et al, 2020 ). With increasing attention, other variable phenotypes of the TUBB8 mutations have also been discovered (Chen et al, 2017a ; Huang et al, 2017 ; Wang et al, 2018 ; Xiang et al, 2018 ; Yuan et al, 2018 ; Jia et al, 2020 ; Xing et al, 2020 ). The same as TUBB8 gene, pathogenic variants in PATL2 was first found to result in GV arrest (Chen et al, 2017b ; Maddirevula et al, 2017 ), and then similar but slightly variable phenotypes were reported (Chen et al, 2017b ; Maddirevula et al, 2017 ; Christou-Kent et al, 2018 ; Huang et al, 2018 ; Wu et al, 2019 ; Liu et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published describing infertility cases with oocyte maturation arrest; however, heterozygous TUBB8 mutations were not discovered during our work on the genetic basis of oocyte arrest until 2016. As of today, some in-vivo studies have been exploring the treatment for infertile patients with TUBB8 mutations [ 30 ]. By injecting WT TUBB8 cRNA into mouse oocytes—where the mutant TUBB8 was expressed—the blastocyst rate was significantly improved and finally acquired normal mouse offspring.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, mutations in TUBB8 contribute to the disruption of oocyte meiotic spindle assembly and maturation and lead to female infertility (Feng et al, 2016). Subsequent studies have also proved through a mutation analysis that the mutation of TUBB8 is related to female infertility, and the mutation causes abnormal phenotypes, including oocyte maturation arrest, oocytes with large polar body, failure of fertilization, and early embryonic arrest (Yuan et al, 2018;Chen et al, 2019;Jia et al, 2020;Zhao et al, 2020). Although PCOS patients have more oocyte yield from stimulation during IVF cycle, poor oocyte quality causes lower fertilization and implantation rates, poor quality of embryos, decreased pregnancy rates, and increased miscarriage rates (Dor et al, 1990;Sengoku et al, 1997;Mulders et al, 2003;Plachot et al, 2003;Heijnen et al, 2006;Weghofer et al, 2007;Sahu et al, 2008;Qiao and Feng, 2011;Rajani et al, 2012).…”
Section: Discussionmentioning
confidence: 99%